2019
DOI: 10.1038/s41598-019-44056-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic, non-intoxicating 8,9-dihydrocannabidiol for the mitigation of seizures

Abstract: There can be a fine line between therapeutic intervention and substance abuse, and this point is clearly exemplified in herbal cannabis and its products. Therapies involving cannabis have been the treatment of last resort for some cases of refractory epilepsy, and this has been among the strongest medical justifications for legalization of marijuana. In order to circumvent the narcotic effects of Δ 9 -tetrahydrocannabinol (THC), many studies have concentrated on its less intoxicating iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 43 publications
0
33
0
2
Order By: Relevance
“…Few studies exist that feature synthetic THC-free CBD and its role in epilepsy [52][53][54][55]. A recent prospective open-label study in pediatric and adult patients with epilepsy showed similar efficacy and tolerance of synthetic CBD compared to plant-derived CBD [54], thus emphasizing the assumed therapeutic similarity of synthetic and plant-derived CBD as both of them are chemically identical [56]. Supporters of plant-derived CBD promote the "entourage effect" as a synergistic interaction between the different compounds of cannabis.…”
Section: Studies With Synthetic Cannabidiolmentioning
confidence: 99%
“…Few studies exist that feature synthetic THC-free CBD and its role in epilepsy [52][53][54][55]. A recent prospective open-label study in pediatric and adult patients with epilepsy showed similar efficacy and tolerance of synthetic CBD compared to plant-derived CBD [54], thus emphasizing the assumed therapeutic similarity of synthetic and plant-derived CBD as both of them are chemically identical [56]. Supporters of plant-derived CBD promote the "entourage effect" as a synergistic interaction between the different compounds of cannabis.…”
Section: Studies With Synthetic Cannabidiolmentioning
confidence: 99%
“…Oxidative Medicine and Cellular Longevity (H2CBD), do not activate the THC pathway, unlike CBD extracts [7,8]. Cardiovascular diseases (CVDs) are the leading cause of mortality worldwide [9].…”
Section: Introductionmentioning
confidence: 99%
“…8,9‐Dihydrocannabidiol ( 96 ), also known as H2CBD, has the structural difference from (−)‐CBD only by the saturated exocyclic C=C bond in the limonene moiety. Despite this subtle difference, H2CBD, an unnatural CBD analog, is reported to have several interesting characteristics compared with (−)‐CBD . In addition to the comparable anticonvulsant effect as seen in the positive control of (−)‐CBD, H2CBD has the inhibitory effect on cytochrome P450 and the antioxidant activity by inhibiting the production of reactive oxygen intermediates, nitric oxide, and tumor necrosis factor in murine macrophage .…”
Section: Limonene Analogsmentioning
confidence: 99%
“…Another advantage of H2CBD (and other synthetic (−)‐CBD analogs in general) would be that it is purely synthetic compound and, thus, free from problems in the uncontrolled Cannabis cultivation and compound extraction (e.g., heavy water usage and use of pesticides/herbicides) . H2CBD was initially synthesized by the terpenylation of olivetol ( 18 ) with the allyl cation derived by p ‐TsOH treatment of α‐phellandrene ( 110 ), and the reaction conditions were optimized further to generate (±)‐H2CBD ((±)‐ 96 ) in higher yield (71 %) (Scheme ) . Their reaction strategy made the gram‐scale synthesis feasible, and it was also anticipated that the single‐step synthesis from food‐grade α‐phellandrene and olivetol would bring practicality to the chemical synthesis.…”
Section: Limonene Analogsmentioning
confidence: 99%